Southern rice black-streaked dwarf virus: a white-backed planthopper-transmitted fijivirus threatening rice production in Asia - Zhou, Guohui; Xu, Donglin; Xu, Dagao; Zhang, Maoxin (Frontiers in Microbiology, 2013)
Southern rice black-streaked dwarf virus (SRBSDV), a nonenveloped icosahedral virus with a genome of 10 double-stranded RNA segments, is a novel species in the genus Fijivirus (family Reoviridae) first recognized in 2008. Rice plants infected with this virus exhibit symptoms similar to those caused by Rice black-streaked dwarf virus. Since 2009, the virus has rapidly spread and caused serious rice losses in East and Southeast Asia. Significant progress has been made in recent years in understanding this disease, especially about the functions of the viral genes, rice–virus–insect interactions, and epidemiology and control measures. The virus can be efficiently transmitted by the white-backed planthopper (WBPH, Sogatella furcifera) in a persistent circulative propagative manner but cannot be transmitted by the brown planthopper (Nilaparvata lugens) and small brown planthopper (Laodelphax striatellus). Rice, maize, Chinese sorghum (Coix lacryma-jobi) and other grass weeds can be infected via WBPH. However, only rice plays a major role in the virus infection cycle because of the vector's preference. In Southeast Asia, WBPH is a long-distance migratory rice pest. The disease cycle can be described as follows: SRBSDV and its WBPH vector overwinter in warm tropical or sub-tropical areas; viruliferous WBPH adults carry the virus from south to north via long-distance migration in early spring, transmit the virus to rice seedlings in the newly colonized areas, and lay eggs on the infected seedlings; the next generation of WBPHs propagate on infected seedlings, become viruliferous, disperse, and cause new disease outbreaks. Several molecular and serological methods have been developed to detect SRBSDV in plant tissues and individual insects. Control measures based on protection from WBPH, including seedbed coverage, chemical seed treatments, and chemical spraying of seedlings, have proven effective in China.